2018
DOI: 10.1002/jbm.a.36437
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of Ni(II) on monocytes and macrophages in normal and hyperglycemic environments

Abstract: Corrosion and release of nickel ions from biomedical alloys are well documented, but little is still known about the effects of released nickel ions on cellular function with recurrent inflammatory challenges. Evidence suggests Ni(II) ions amplify LPS-induced secretion of several pro-inflammatory cytokines from monocytes. Exacerbating the inflammatory response, hyperglycemic conditions also affect monocytic function. This study investigated how Ni(II) and hyperglycemic conditions, both singly and in combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…The analysis of cell number and cellular activity revealed the impact of metal ions on metabolic activity by showing a significant decrease in activity that was mainly prominent in 500 μM cobalt-and nickel ion-treated cells. Similar results for nickel ions were reported by Chana et al [13]. The loss of metabolic activity was accompanied by a massive release of reactive oxygen species.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The analysis of cell number and cellular activity revealed the impact of metal ions on metabolic activity by showing a significant decrease in activity that was mainly prominent in 500 μM cobalt-and nickel ion-treated cells. Similar results for nickel ions were reported by Chana et al [13]. The loss of metabolic activity was accompanied by a massive release of reactive oxygen species.…”
Section: Discussionsupporting
confidence: 89%
“…As found by us (data not shown) and also reported by Lund et al [12], THP-1 derived macrophages de-differentiate, detach from the surface of the cell culture dish and show a round monocyte-like morphology after more than 48 h without PMA. However, the simultaneous presence of PMA in THP-1 macrophage culture was shown to interfere with the effects of nickel ions [13]. We therefore decided to differentiate for 24 h with PMA, to then remove PMA from the cell culture and to limit the incubation time with metal ions to 48 h.…”
Section: Cell Culturementioning
confidence: 99%
“…The higher prevalence of nickel allergy in obese individuals (Lusi et al, 2015) was associated with a worse metabolic profile, while reducing the oral intake of nickel led to a considerable reduction in the BMI (Lusi et al, 2015;Watanabe et al, 2018). Chana et al (2018) confirmed that nickel (II) amplifies LPS-induced secretion of several pro-inflammatory cytokines from monocytes. It is known that hyperglycaemic conditions also affect monocytic function.…”
Section: Immunotoxic Activity Of Nickelmentioning
confidence: 69%
“…Chana et al. (2018) confirmed that nickel (II) amplifies LPS‐induced secretion of several pro‐inflammatory cytokines from monocytes. It is known that hyperglycaemic conditions also affect monocytic function.…”
Section: Assessmentmentioning
confidence: 95%
“…Ni 2+ also activates the expression of intercellular adhesion molecules on endothelial cells and keratinocytes, therefore amplifying the inflammatory response [66]. More recently, Ni 2+ and particularly NiSO 4 has been shown to alter inflammatory cytokine secretion from monocytes [67] by modulating transcription factor signaling pathways such as the nuclear factor kappa B (NF-kB), that regulate cytokine secretion [68, 69]. However, Ni 2+ does not alter the activation or nuclear translocation efficiency of NF-kB [70]; emerging evidence suggest that redox status generated by Ni 2+ regulates the nuclear activity of NF-kB proteins [71] by altering the binding of NF-kB proteins to DNA [70].…”
Section: Discussionmentioning
confidence: 99%